The role of the co-curricular Musabaqoh Hifdzil Quran in developing the current Quranic generation at Sabilul Muhtadin Junior High School Karangasem Jenu - Kholifatun Nisa; Qomariyatul Ilmiyah (Institution of Scientific Publishing and Publication of the Yayasan Dzaky Elmumtaz Qurani, 2025)
This study aims to analyze the role of the Musabaqoh Hifdzil Qur’an (MHQ) cocurricular program in nurturing a Qur’anic generation at SMP Sabilul Muhtadin Karangasem Jenu. The research employs a descriptive qualitative approach with a case study model through observation, in-depth interviews, and documentation. The findings indicate that the implementation of MHQ is systematically organized through memorization-level grouping, the application of the one day one ayat method, regular muroja’ah sessions, Fashoha practice, and periodic evaluations such as PTS and tasmi’. The program not only improves students’ abilities in reading, memorizing, and understanding the meaning of Qur’anic verses, but also shapes students into a more holistic Qur’anic generation. The integration of MHQ into daily religious routines at school further strengthens students’ spiritual, cognitive, and affective development. Overall, the study concludes that MHQ plays a significant role as an effective program for fostering comprehensive Qur’anic character in students and is suitable to be used as a model for Qur’an-based religious development in formal educational settings.